Efektivitas Pelaksanaan Asas Akuntabilitas Oleh Otoritas Jasa Keuangan (OJK) Dalam Pengawasan Sektor Keuangan Digital Diindonesia - Gabriella Riato, Grace; Tiurlan Catherine, Verina (CV. Green Publisher Indonesia, 2025)
The development of information technology has changed the landscape of the financial industry in Indonesia through the presence of various digital financial services, such as peer-to-peer lending, digital wallets, and neobanks. This transformation provides easy access for the public, but at the same time poses new challenges in terms of supervision and consumer protection. Therefore, the application of the principle of accountability by the Financial Services Authority (OJK) is crucial to ensure financial system stability and public trust. This study aims to analyze the effectiveness of the implementation of the principle of accountability by the OJK in the supervision of the digital financial sector in Indonesia. The research method used is normative juridical with a statute approach and a case approach, through an analysis of regulations related to digital finance and a number of cases of violations committed by digital financial service providers. The results of the study show that normatively the OJK has applied the principle of accountability through the formation of regulations, public reporting mechanisms, policy transparency, and enforcement of administrative sanctions. However, the effectiveness of its implementation still faces various obstacles, such as rapid technological development, limited human resources, high illegal fintech practices, and weak coordination between supervisory agencies. This study concludes that strengthening the principle of accountability by the OJK requires adaptive regulatory reform, the use of supervisory technology (suptech), and institutional capacity building to deal with the complexity of risks in the digital financial sector.